2016
DOI: 10.1016/j.chemgeo.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium zinc isotope fractionation in Zn-bearing minerals from first-principles calculations

Abstract: Isotopic composition analysis contributes significantly to the investigation of the biogeochemical cycle of zinc with its economical, environmental and health implications. Interpretation of isotopic measurements is however hindered by the lack of a set of equilibrium isotopic fractionation factors between Zn-bearing minerals. In this study, equilibrium mass-dependent Zn isotope fractionation factors in Zn-bearing minerals are determined from first-principles calculations within the density functional theory (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
55
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 95 publications
11
55
1
Order By: Relevance
“…The temperatures required to decrease the 66/64 Zn fractionation factor of eq. 5, Δ 66 ZnZnO(s)-Zn(g), to analytically unresolvable levels (<0.05‰) are >2200°C (given Δ 66 ZnZnO(s)-Zn(g) = +0.31×10 6 /2473 2 = +0.05‰; Ducher et al, 2016). Thermodynamic data for eq.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperatures required to decrease the 66/64 Zn fractionation factor of eq. 5, Δ 66 ZnZnO(s)-Zn(g), to analytically unresolvable levels (<0.05‰) are >2200°C (given Δ 66 ZnZnO(s)-Zn(g) = +0.31×10 6 /2473 2 = +0.05‰; Ducher et al, 2016). Thermodynamic data for eq.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, which end-member scenario characterises volatile loss during planetary formation, remains unconstrained, despite the fact that these processes may be distinguished by their stable isotope signatures. Namely, equilibrium isotope fractionation of Zn between condensed phase(s) and gas is smaller, especially at high temperatures (the 66 Zn/ 64 Zn fractionation factor between ZnO(s) and Zn 0 (g) is 0.31‰×10 6 /T 2 ; Ducher et al, 2016), than kinetically-driven vapour loss into a vacuum which is temperature-independent and scales with the inverse square root of the masses of the two evaporating isotopes (cf. Richter et al, 2002).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…1‰ lighter than the original sample (Weiss et al, 2014). Ducher et al (2016) reported theoretical studies of Zn isotope fractionation in Zn-bearing minerals. They investigated the isotope fractionation properties of Zn in several minerals at equilibrium using density functional theory (DFT).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This means that, at equilibrium, an alteration process that releases Zn from sphalerite and reprecipitates it into secondary minerals could produce either positive or negative fractionations: hemimorphite and hydrozincite would be isotopically heavier than parental sphalerite (at 22 °C ∆ hem-sph (‰) = +1.38, ∆ hydr-sph (‰) = +0.80), whereas smithsonite would be isotopically lighter (at 22 °C ∆ sm-sph (‰) = -0.10). Crystalchemical parameters control these isotopic properties (Ducher et al, 2016): indeed, excellent linear correlations exist between ln β and Zn interatomic force constants, and β-factors increase when the Zn-first neighbor bond lengths decrease and charges on atoms involved in the bonding increase and vice versa.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A larger Zn isotope fractionation has been reported in recent experiments, where the adsorption of Zn onto calcite can fractionate Zn isotopes, with Δ 66 Zn adsorbed-solution = 0.41 ± 0.18‰ at low ionic strength and 0.73 ± 0.08‰ at high ionic strength (Dong & Wasylenki, 2016). Nevertheless, all observed Zn isotope fractionation under natural conditions are much different from that of theoretical calculations (Δ 66 Zn hydrozincite-solution = 1.0‰, Fujii et al, 2011Fujii et al, , 2014; Δ 66 Zn smithsonite-solution = À0.73‰, Ducher et al, 2016).…”
Section: Zn Isotope Composition Of Zn Associated With Carbonatementioning
confidence: 71%